Práticas de coordenação no canal de distribuição da cadeia automotiva - Ferreira, Heloisa Sousa Ribeiro (2006)
The main change in modern businnes management is the supply chain building and management, due to increasing need to turn them more competitive, in result of the recognition that the competition, in these days, happens between supply chains, no more between isolated business. Besides managing its internal activities, the supply chain management has the challenge of coordinating and managing its partners, including suppliers and customers. The references indicate some organizational and management tools that can help in performing those activities, and in this paper, they will be called coordinating practices to suplly chain management. This paper focus is to analyse the application of some tools in the automotive channel, and the main objectives are: identify and evalute the benefits performance reached through the use and application of some coordinating practices in automotive supply chain, focalizing the relationship between industry and channel, formed by car dealerships. The secondary objectives are: identify power, dependende and conflict relationships between OEM and channel; define the leadership and control; verify the main franchising contracts characteristics; identifiy the impact and the benefits of coordinating iniciatives in different car dealership sizes. Among its reasons, this paper aims to fill out the gap in researched literature, marked by few academic studies with unit of analysis in car vehicles distribution or in industry-distribution channel relationship. In this paper, the research type is a exploratory survey in one of the four main automotive industries in country, and in its respective channel. Expecting that the research results improve the practices applicability, and also help both industry and dealerships in managing the existing relationship.